On the incidence of renewable energy subsidies into land prices - Evidence from Germany - Martin Simmler; Peter Haan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In 2012, the subsidy for electricity produced by wind turbines - introduced with the Renewable Energy Act (REA) in Germany 2000 - amounts to almost 14 billion Euros or roughly 100% of the corporate income tax revenue. The central aim of this subsidy is to foster investment into renewable energy sources by providing long run financial security. In this analysis, we study the incidence of this subsidy on land prices. Our empirical design exploits variation over time in the return of wind turbines due to the introduction of the REA and relates it to changes in transaction prices for agricultural land for 250 non-urban counties between 1997 and 2012. We employ an instrumental variable estimator to ensure unbiased coefficients despite the endogeneity of the plants' location decision. We find that 11% of the subsidy paid to wind turbine investors is capitalized into land prices. Accounting for investor's costs, the share raises to 24% of investor's profits. The results are robust for a wide range of specifications.
Keywords: H23; H22; Q42; 330